Anxiety after Stroke: Time for an Intervention. Issue 5 (July 2015) - Chun, Ho-Yan Yvonne; Whiteley, William N.; Carson, Alan; Dennis, Martin; Mead, Gillian E.
Anxiety is common and persistent after stroke, and is associated with a poorer quality of life. Guidelines from numerous countries, including the United Kingdom, recommend screening for poststroke emotional problems. Anxiety is a priority for the National Institute for Health and Care Excellence, stroke charities, and stroke survivors in the United Kingdom. Yet there is little evidence to guide the management of anxiety after stroke. New evidence-based interventions are needed to improve the care of poststroke anxiety.